MANAJEMEN PERPUSTAKAAN SEKOLAH MA ANWARUL HASANIYAH (ANWAHA) KABUPATEN TABALONG - M. Yarni; M. Ridha; M. Ruhi; M. Ramadani; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The library is one of the supporting components in an academic institution, namely it plays an important role in providing books as a source of learning reference. Therefore, libraries must also be equipped with good information systems so that the role of libraries in academic institutions is maximized. The aim of this research is to build a library information system that can facilitate book data collection, digital book document storage and record book circulation in the library at the Ma Anwarul Hasaniyah (ANWAHA) school. And also library management is basically the process of optimizing human, material and budget contributions to achieve library goals. The library at Ma Anwaha school is still experiencing several obstacles, so it cannot run as it should. These obstacles come from two aspects. Firstly, the structural aspect, meaning that the existence of the library at Ma Anwaha's school has received little attention from the school management. Second, the technical aspect, meaning that the existence of the library at Ma Anwaha's school has not been supported by technical aspects that are really needed by school libraries such as funds and facilities and infrastructure.